Original paper Allergic and nonallergic rhinitis in schoolchildren. Part II. Relationship to spirometric parameters, bronchial hyperresponsiveness and biomarkers of allergic inflammation - Lis, Grzegorz; Twarduś, Krystyna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2011)
Introduction : In recent years, with the increasing prevalence of allergic rhinitis (AR), a higher incidence of nonallergic rhinitis (NAR) has been observed. Aim : The aim of the study was the comparison of pulmonary function tests and the degree of bronchial hyperresponsiveness (BHR) in children with AR and NAR, evaluation of the biomarker for clinical AR or BHR diagnosis. Material and methods : Pulmonary function tests and BHR in the exercise tests were done in 139 schoolchildren (8-14 years of age) with symptoms of non-infectious rhinitis. The analyzed biomarkers included exhaled nitric oxide (FeNO), total IgE (tIgE), serum IL-4, serum tumour necrosis factor α (TNF-α), absolute eosinophils count in blood (Eos). Positive prick tests with 10 aeroallergens identified children with AR. Results : Spirometric parameters and values of BHR were not different in AR (n = 73) and NAR (n = 66) groups. The risk of BHR was higher in children with AR than those with NAR (OR = 2.768; p = 0.051). In the logistic regression analysis, none of the analyzed biomarkers was related to BHR. Differences in the area under the ROC curve (AUC) for: tIgE and FeNO (AUC tIgE -AUC FeNO = 0.102; p = 0.042), FeNO and Eos (AUC FeNO -AUC Eos = 0.07; p = 0.219), tIgE and Eos (AUC tIgE -AUC Eos = 0.172; p = 0.002) showed that measurements of tIgE level were the best diagnostic tool for AR (sensitivity = 78.9%, specificity = 79.4% for tIgE = 68 kU/l). Conclusions : There were no differences in pulmonary function test parameters between groups of children with AR and NAR. Bronchial hyperresponsiveness was more often observed in AR than in NAR. Any biomarker of allergic inflammation predicts BHR in children with rhinitis. The accuracy of diagnostic AR testing with tIgE measurement (cut-off level = 68 kU/l) was moderately good in schoolchildren.